Outsiders in a promised land : religious activists in Pacific Northwest history - Soden, Dale Edward (Oregon State University Press, 2015)
"Outsiders in a Promised Land explores the role that religious activists have played in shaping the culture of the Pacific Northwest, particularly in Washington and Oregon, from the middle of the 19th century onward. The region's earliest settlers came to work in the mines and forests, and a culture of saloons, gambling halls, and brothels grew up to serve them. When migration to the region intensified, newcomers with families and religious traditions often saw themselves as outsiders in opposition to the prevailing frontier culture. As communities grew in population, early activists found common ground in a desire to protect women and children, and make their towns more hospitable to religious values. Protestants, Catholics, and Jews worked together to transform communities. Together they introduced public and private schools, health care institutions, libraries and orphanages, and lobbied for the prohibition of alcohol. Beginning in the 1930s, religious activism played a crucial role in the emerging culture wars between liberals and conservatives. Liberals rallied around the protection of civil rights and the building of social safety nets, while conservatives decried the rise of secularism, liberalism, and communism. Today, religious activists of many faiths are deeply engaged in matters related to women's and gay rights, foreign policy, and environmental protection. Outsiders in a Promised Land is a meticulously researched, comprehensive treatment of religion in Pacific Northwest public life from the middle of the nineteenth century to the present. The first book of its kind, it is destined to be an essential reference for scholars, activists, and religious leaders of all faiths. "--